2000
DOI: 10.1111/1468-0343.00069
|View full text |Cite
|
Sign up to set email alerts
|

Causality and Feedback Between Institutional Measures and Economic Growth

Abstract: Recent cross-section studies have demonstrated a strong link between measures of corruption, bureaucratic quality, property rights, and other institutional variables, and economic growth. In this paper we build on previous research and present some empirical evidence on the direction of causality between institutional measures and growth. It appears that the poorer the country, and the longer the wait, the higher the in¯uence of institutional quality on economic growth. However, we also show the existence of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
168
0
10

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(192 citation statements)
references
References 10 publications
14
168
0
10
Order By: Relevance
“…These findings are consistent with those reported by Chong and Calderón (2000a), who also used the ICRG's corruption and bureaucratic quality variables. They reported that corruption had no impact on growth, while bureaucratic quality was significant only at the 10% level.…”
Section: Empirical Results: Growthsupporting
confidence: 91%
“…These findings are consistent with those reported by Chong and Calderón (2000a), who also used the ICRG's corruption and bureaucratic quality variables. They reported that corruption had no impact on growth, while bureaucratic quality was significant only at the 10% level.…”
Section: Empirical Results: Growthsupporting
confidence: 91%
“…Environments, in which economic returns can be easily secured through formal institutions, foster the cooperation of economic agents. Studies have demonstrated a strong link between institutional environment (measured through corruption, bureaucratic quality, property rights and other institutional variables, or what in social capital literature is considered as government social capital) and economic growth [9][10][11]. Government can secure property rights and enforce contracts by formal institutions, but "rules on the book" might be very different from what actually takes place in a country [12].…”
Section: Introductionmentioning
confidence: 99%
“…9 In particular, we use the ratio of public consumption to GDP, the ratio of fiscal deficits to GDP, population (in logs), share of urban population, civil liberties, political rights, rule of law, corruption by the government, standard deviation of inflation, inflation rate, age dependency ratio, growth in GDP per capita, PPP GDP deviations, PPP Investment deviations, regional dummies, ratio of Exports to GDP, and degree of openness. 10 Among others, Chong and Calderón (2000) provide an application of the method.…”
Section: Discussionmentioning
confidence: 99%